Single step BP/LR combined Gateway reactions. (November 2013) - Liang, Xiquan; Peng, Lansha; Baek, Chang-Ho; Katzen, Federico
The Gateway recombination system is characterized by its ability to transfer DNA sequences back and forth between an intermediate clone (the entry clone) and a variety of destination vectors. However, a number of applications do not need to exploit the advantages offered by the entry clone. Here we report reaction conditions for cloning DNA fragments into destination vectors in a single step reaction, thus reducing the cost and overall time needed to obtain an expression clone from three days to one.